Analisis risiko bisnis expedisi dengan melakukan pendekatan proses di RBT transport - Agustina, Ade (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The land transportation system is one of the important elements in promoting economic growth in Indonesia. Of course, companies engaged in this transportation service or we are better known as expedition companies have many challenges that will be faced especially the main processes in this business are outside the field far from the supervision of the business owner. So it is important for business owners to carry out a risk analysis of what is being carried out to keep the company alive. In this paper, the method used in this research is descriptive qualitative by analyzing the operational, financial and external process approaches. The high number of land traffic accidents, the government continues to make improvements to the system and regulations to reduce the number of accidents, one of which is the supervision of freight transport.